Cross-restriction of a T cell clone to HLA-DR alleles associated with rheumatoid arthritis: clues to arthritogenic peptide motifs. - Hawke, S; Matsuo, H; Nicolle, M; Wordsworth, P; Corlett, L; Spack, E; Deshpande, S; Driscoll, P; Willcox, N (Lippincott Williams and Wilkins, 1999)
OBJECTIVE: To identify distinctive sequence motifs required for productive peptide presentation by those HLA-DR alleles/DR4 subtypes that predispose to rheumatoid arthritis (RA). METHODS: We tested 10 different HLA-DR4 subtypes for presentation of acetylcholine receptor peptides to 8 different DR4-restricted T cell lines/clones in proliferation assays. RESULTS: Seven of the 8 T cells depended absolutely on either the autologous Lys71 (in Dw4) or Arg71 (e.g., Dw14), despite these alleles' similar charge and RA associations. In contrast, the PM-A T cell was only mildly affected by this interchange. Moreover, after minor modifications, peptides were presented to this unusual T cell preferentially by all the RA-associated subtypes of DR4 as well as by 2 other DR alleles (DR1 and DR1402) that predispose to RA. CONCLUSION: This coincident cross-restriction to all the RA-associated HLA-DR alleles except DR10 shows that there could even be a single arthritogenic peptide; we now suggest a possible consensus motif.